Efficient Channel Management Mechanism to Enhance Channel Utilization for Sensing Data Delivery in Vehicular Ad Hoc Networks. (26th August 2015) - Tsogoo, Buyandelger; Yoo, Sang-Jo
Abstract : IEEE 1609.4 defines MAC layer implementation in a vehicular ad hoc network (VANET). In IEEE 1609.4 multichannel operation, the control channel interval (CCHI) and the service channel interval (SCHI) are defined such that service channels cannot be utilized during the CCHI, and vice versa, which leads to poor utilization of scarce spectrum resources. In this paper, we propose a multi-schedule-based channel switching mechanism to improve channel utilization and uniformly distribute channel load. In our proposed mechanism, four schedules are defined to switch between the control channel and service channels. Therefore, service channels can be utilized during the CCHI, and the control channel can be utilized during the SCHI. Moreover, control channel load is distributed throughout the whole sync interval. We compared our proposed MAC protocol with IEEE802.11p for wireless access in the vehicular environment using the OMNET++ 4.5 network simulator. In the simulation results, we determined that utilization of the service channel increased and contention on the control channel was reduced, compared with the legacy standard, especially in slow motion and high-density VANETs.